MODAL SOSIAL: KONSEP DAN APLIKASI - Rusydi Syahra (LIPI Press, 2003)
This article is aimed at explaining the development of social capital theory and its contribution in addressing social problems. Despite its first introduction in the early 20th century by Lyda Judson Hanifan the term social capital has gained prominence in social science only since its reintroduction by James Coleman in 1988 and through the subsequent work of Robert Putnam. Social capital defined by Putnam as features of social organization such as networks, trust and norms of reciprocity that facilitate cooperation for mutual benefits, has inspired many social scientists to conduct studies on the conditions of social capital in various communities in many countries. Interestingly, some of the studies have contributed to the enrichment of the social capital theory by introducing new related concepts and methods of measurement. On the practical side social capital has gained wider recognition by international aid agencies, especially the World Bank, and has been used as a powerful concept for poverty alleviation through people empowerment in many developing countries, including Indonesia.